Tobacco Smoking in Early Adulthood and Labor Market Performance: The Cardiovascular Risk in Young Finns Study - Viinikainen, Jutta; Böckerman, Petri; Hakulinen, Christian; Kari, Jaana T; Lehtimäki, Terho; Pahkala, Katja; Pehkonen, Jaakko; Viikari, Jorma; Raitakari, Olli T (Oxford University Press (OUP), 2025)
Introduction: Tobacco smoking has been associated with reduced success in the labor market, potentially due to its negative impact on labor productivity, especially in physically demanding jobs, as it affects physical fitness and performance adversely.
Methods: This prospective study used data from the Cardiovascular Risk in Young Finns Study survey, linked to register information on labor market outcomes and education attainment, to examine the association between tobacco smoking and long-term labor market outcomes (earnings and employment, N = 1953). Smoking levels were determined by cigarette pack-years in 2001, as reported in the survey, whereas annual earnings and employment status were tracked from 2001 to 2019.
Results: A one-unit increase in pack-year of smoking was associated with a 1.8% decrease in earnings (95% confidence interval [CI]: -2.6% to -0.9%) and a 0.5% reduction in years employed (95% CI: -0.6% to -0.3%). This association was pronounced among participants with lower education levels. The earnings difference was evident among younger cohorts, whereas a negative correlation with employment was observed most strongly in older cohorts among individuals with lower education.
Conclusions: Our findings suggest that smoking had a negative effect on earnings among the younger generation, particularly among the less well-educated. The finding of greater impacts on years of employment among the older age group, particularly among groups with low education levels, is consistent with the delayed onset of most health impacts, which may particularly affect productivity in physically demanding jobs that are more common among people with less education.
Implications: Adverse consequences of smoking include reduced earnings and labor market participation, particularly among less well-educated groups. Tobacco control advocates should draw attention to these consequences in arguing for effective measures to reduce smoking initiation and increase cessation in order to achieve socially optimal outcomes.